Changes in Ecological Charges in Water Management in the Light of Recent Water Law - Małecki, Piotr P.; Thier, Agnieszka (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
This paper presents the general issue of charges and rising rates for water and an assessment of the economic and social consequences thereof following the enforcement of a new water law. The authors present the issue and the constituent parts of ecological charges related to water management. They then analyse the changes taking place within that system, which involve extending the range of charges, limitation of exemptions and liquidation of breaks as well as a dramatic increase in charges. The authors analyse and show the consequences of increasing charges for water in selected sectors of the economy, highlighting the bottling industry and individual households. They also signal the possible decreases in the charges for the use of water supply network in the selected gminas and the potential breaks in charges for the least advantaged members of the community.